2021
DOI: 10.3390/agriculture11070672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Packing Density on the Bacterial Community, Fermentation, and In Vitro Digestibility of Whole-Crop Barley Silage

Abstract: Packing density has a significant influence on the outcome of ensiling forage. In this study, we aim to investigate the effect of packing density on the ensiling properties, microbiome, and in vitro digestibility of barley silages. Barley was ensiled in polyethylene drum silos (30 L) with respective densities of 600, 650, 700, and 750 kg/m3 fresh matter (FM), and stored for 60 days. The bacterial communities, fermentation quality, and in vitro digestibility were analyzed. Fresh barley had a low count of lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
3
22
1
Order By: Relevance
“…These results suggested that heterofermentative LAB might dominate the fermentation process of sorghum-sudangrass silage under low storage temperature (Cai et al, 1998). In the present study, Pantoea was one of the main bacterial genera (6.18-11.35%) in sorghum-sudangrass silage; moreover, Pantoea exhibits increasing abundance as the most dominant bacterial genus during the initial aerobic phase of whole-plant corn silage (Sun et al, 2021a). However, the effect of Pantoea on silage is not clear and requires further study.…”
Section: Microbial Counts and Bacterial Community In Silagesupporting
confidence: 51%
See 4 more Smart Citations
“…These results suggested that heterofermentative LAB might dominate the fermentation process of sorghum-sudangrass silage under low storage temperature (Cai et al, 1998). In the present study, Pantoea was one of the main bacterial genera (6.18-11.35%) in sorghum-sudangrass silage; moreover, Pantoea exhibits increasing abundance as the most dominant bacterial genus during the initial aerobic phase of whole-plant corn silage (Sun et al, 2021a). However, the effect of Pantoea on silage is not clear and requires further study.…”
Section: Microbial Counts and Bacterial Community In Silagesupporting
confidence: 51%
“…These results also explained the satisfactory fermentation quality of the silage in the present study. There was no difference in Lactobacillus in sorghum-sudangrass silage between high and LD (Figure 3); however, Sun et al (2021a) reported that increasing density could enhance the abundance of Lactobacillus in barley silage. This difference might be due to differences in characteristics of forage before ensiling.…”
Section: Microbial Counts and Bacterial Community In Silagementioning
confidence: 93%
See 3 more Smart Citations